1985
DOI: 10.1007/bf02174059
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the spitting cobra ophthalmia (Naja nigricollis)

Abstract: Experimental studies were conducted to investigate the clinical and morphological effects of various doses of Naja nigricollis venom (0.1-5.0 mg) on the eyes of rabbits. Our findings suggest that in the early stage of the ophthalmia caused by the spitting cobra, specific fractions of the venom are responsible for the nitrogen mustardlike effect. However, the further course seems to be determined by liberated inflammation mediators like prostaglandins and leukotrienes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Cobra ( N. nigricollis ) venom was shown to penetrate the corneal epithelium and bind to the corneal stroma. Corneal complications occurred 30 min after initiation and reached the maximum severity at 12 h [ 49 ], displaying nitrogen mustard-like effects (similar to chemical burn) on rabbit corneas [ 50 ]. To compare the effects of venom from different snake species, a group conducted an ex vivo eye irritation test (EVEIT) [ 51 ] and found that venoms from spitting elapids Naja ( N. mossambica, N. nigricollis ) but not non-spitting vipers ( Bothrops jararaca and B. lanceolatus ) cause increased thickness of rabbit corneas [ 51 ].…”
Section: Pathophysiology Of Venom Induced Ocular Complicationsmentioning
confidence: 99%
“…Cobra ( N. nigricollis ) venom was shown to penetrate the corneal epithelium and bind to the corneal stroma. Corneal complications occurred 30 min after initiation and reached the maximum severity at 12 h [ 49 ], displaying nitrogen mustard-like effects (similar to chemical burn) on rabbit corneas [ 50 ]. To compare the effects of venom from different snake species, a group conducted an ex vivo eye irritation test (EVEIT) [ 51 ] and found that venoms from spitting elapids Naja ( N. mossambica, N. nigricollis ) but not non-spitting vipers ( Bothrops jararaca and B. lanceolatus ) cause increased thickness of rabbit corneas [ 51 ].…”
Section: Pathophysiology Of Venom Induced Ocular Complicationsmentioning
confidence: 99%
“…The spitting cobra can eject its venom several meters into the eyes of its victim. [51][52][53][54] The venom can cause severe chemosis, blepharitis, and corneal irritation. Opacification with corneal and subconjunctival neovascularization (termed the "corneal opacification syndrome") often leads to blindness and is most often associated with the black cobra (Naja nigricollis).…”
Section: Chemical Eye Injuriesmentioning
confidence: 99%
“…Opacification with corneal and subconjunctival neovascularization (termed the "corneal opacification syndrome") often leads to blindness and is most often associated with the black cobra (Naja nigricollis). 51,52 There is some evidence from rabbit studies that tetracycline drops and systemic heparin have a protective effect in guarding against corneal opacification syndrome. 51 Currently, there is no indication for topical or intravenous antivenom administration following an eye exposure to cobra venom.…”
Section: Chemical Eye Injuriesmentioning
confidence: 99%
“…The spitting cobra can eject its venom several meters into the eyes of its victim. 51 The venom can cause severe chemosis, blepharitis, and corneal irritation. Opacification with corneal and subconjunctival neovascularization (termed the "corneal opacification syndrome") often leads to blindness and is most often associated with the black cobra (Naja nigricollis).…”
Section: Chemical Eye Injuriesmentioning
confidence: 99%